Odpowiedzi

Najlepsza Odpowiedź!
2010-02-08T19:16:23+01:00
A:2x+3x+(x-5y)=3x-2y
2x+3x+x-5y=3x-2y
6x-5y=3x-2y
6x-3x=-2y+5y
3x=3y/3
x=y
B:12x-(2x+1)-9(2-x)=19x
12x-2x-1-18+9x=19x
19x-19=19x
19x-19x=19
0=19
C:3(x+21)+(2x-3)=5x
3x+63+2x-3=5x
5x+60=5x
5x-5x=-60
0=-60
D:2x+3(x+2)=6(x+1)-x
2x+3x+6=6x+6-x
5x+6=5x+6
5x-5x=6-6
0=0
tożsamosciowe
3 5 3
2010-02-08T19:18:42+01:00
A: 2X+3X+(X-5Y)=3X-2Y
5X+X-5Y=3X-2Y
6X-3X=-2Y+5Y
3X=3Y
X=Y

B: 12x-(2x+1)-9(2-x)=19x
12X-2X-1-18+9X=19X
19X-19=19X
0=19

C: 3(x+21)+(2x-3)=5x
3X+63+2X-3=5X
5X+60=5X
O=60

D: 2x+3(x+2)=6(x+1)-x
2X+3X+6=6X+6-X
5X+6=5X+6
0=0